Designing a Secretory form of RTX-A as an Anticancer Toxin: An In Silico Approach - Taheri-Anganeh, Mortaza; Nezafat, Navid; Gharibi, Saba; Khatami, Seyyed H.; Vahedi, Farzaneh; Shabaninejad, Zahra; Asadi, Marzieh; Savardashtaki, Amir; Movahedpour, Ahmad; Ghasemi, Hassan (Recent Patents on Biotechnology, 2024)
Background: Cancer is a leading cause of death and a significant public health issue worldwide. Standard treatment methods such as chemotherapy, radiotherapy, and surgery are only sometimes effective. Therefore, new therapeutic approaches are needed for cancer treatment. Sea anemone actinoporins are pore-forming toxins (PFTs) with membranolytic activities. RTX-A is a type of PFT that interacts with membrane phospholipids, resulting in pore formation. The synthesis of recombinant proteins in a secretory form has several advantages, including protein solubility and easy purification. In this study, we aimed to discover suitable signal peptides for producing RTX-A in Bacillus subtilis in a secretory form. Methods: Signal peptides were selected from the Signal Peptide Web Server. The probability and secretion pathways of the selected signal peptides were evaluated using the SignalP server. ProtParam and Protein-sol were used to predict the physico-chemical properties and solubility. AlgPred was used to predict the allergenicity of RTX-A linked to suitable signal peptides. Non-allergenic, stable, and soluble signal peptides fused to proteins were chosen, and their secondary and tertiary structures were predicted using GOR IV and I-TASSER, respectively. The PROCHECK server performed the validation of 3D structures. Results: According to bioinformatics analysis, the fusion forms of OSMY_ECOLI and MALE_ECOLI linked to RTX-A were identified as suitable signal peptides. The final proteins with signal peptides were stable, soluble, and non-allergenic for the human body. Moreover, they had appropriate secondary and tertiary structures. Conclusion: The signal above peptides appears ideal for rationalizing secretory and soluble RTX-A. Therefore, the signal peptides found in this study should be further investigated through experimental researches and patents.
Keywords: actinoporins